Warunkowe zwolnienie z odbycia reszty kary skazanych odbywających karę pozbawienia wolności w różnych systemach jej wykonywania - Nawój-Śleszyński, Aldona (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Imprisonment under existing Penal Code will be served in three systems: in intended action system, in a therapeutic system and in an ordinary system.Particularly the intended action system and the therapeutic system have an intensive impact on the criminogenic factors of the convicted. Therefore these systems should generate positive criminological prognosis, which are material assumptions for an early release. The statistical analysis in this article for the period 2009–2014 shows that more than 40% of the conditional early releases that have been granted in Poland are on the request of the convicted person, who often served their sentences in an ordinary system and in a closed prison. It is a great defeat of the prison personnel in their criminological forecasts.
Keywords: warunkowe przedterminowe zwolnienie; kara pozbawienia wolności; systemy odbywania kary pozbawienia wolności; prognozy kryminologiczne; praktyka warunkowego przedterminowego zwolnienia; polityka penitencjarna